Percepatan Pengembangan Varietas Unggul Baru Padi melalui Unit Pengelola Benih Sumber - Ade Supriatna; Joko Mulyono; Zakiah Zakiah (Iptek Tanaman Pangan, 2011)
Previous study was conducted in 2008 in Central Java, in order to identify the following items: (i) the development of seed production in the area and its distribution; (ii) the model of seed industry; and (iii) to analyze the economic visibility of seed industry. Data were collected from 15 seed grower farmers and 25 rice farmers. Secondary data were collected from the Assessment Institute for Agriculture Technology (BPTP)-Central Java, the Office of Agriculture, the Institute for Seed Inspection and Certification (BPSB), the Seed Farm of Food and Horticulture Crops (KBPH), the Central Agency of Statistics (BPS), and the Institute of Agricultural Research. During 2007 BPTP produced 17,454 kg rice seed consisted of SS seed (88.1%) and FS seed (11.9%). The varietal reference test indicated that farmers prefer more of three varieties, namely Mekongga, Cibogo, and Cigeulis. Seed distribution from UPBS to farmers was channeled through the seed dissemination program, the cooperative of seed growers, free seed assistance to support the National Program for Rice Production (P2BN), and through public sales. Model of Seed Industry in the BPTP-Central Java was acting as the Units of Seed Source Development (UPBS). This Institution purchases BS seed from the Indonesian Center for Rice Research (ICRR) and produced FS and SS seeds. Its products were distributed to the KBPH and other local seed growers to produce SS or ES seed that will be planted by farmers. Seed production of rice obtained benefit of Rp 5.5 million/ha/season or 25 present more than that of the rice for consumption, with R/C 1.53. If farmers produced and processed the seed, they would obtain benefit of Rp 19.7 million/ha/season derived from the producing seed (28.1%) and the processing seed (71.9%). The economic performance of seed industry is profitable to farmers, and it supports the shortage of seed supply in Central Java. It needs some cooperation from other institutions, including the supply of BS and FS seeds from ICCR, and cooperation with the existing seed industries for seed distribution.